2007
DOI: 10.1016/j.cmet.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Akt1 Leads to Severe Atherosclerosis and Occlusive Coronary Artery Disease

Abstract: The Akt signaling pathway controls several cellular functions in the cardiovascular system; however, its role in atherogenesis is unknown. Here, we show that the genetic ablation of Akt1 on an apolipoprotein E knockout background (ApoE(-/-)Akt1(-/-)) increases aortic lesion expansion and promotes coronary atherosclerosis. Mechanistically, lesion formation is due to the enhanced expression of proinflammatory genes and endothelial cell and macrophage apoptosis. Bone marrow transfer experiments showing that macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
251
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(270 citation statements)
references
References 38 publications
16
251
1
2
Order By: Relevance
“…It has been convincingly reported that PI3K and Akt are important upstream regulators of eNOS activation. 27,28,[39][40][41][42] eNOSderived NO has been known to have a pivotal role in the modulation of vascular tone and function. 6,7 Taken together, our results allow us to propose that, ROS/RNS excess in peripheral resistance vessels during I/R injury may blunt PI3K/Akt/eNOS pathway, thus triggering endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been convincingly reported that PI3K and Akt are important upstream regulators of eNOS activation. 27,28,[39][40][41][42] eNOSderived NO has been known to have a pivotal role in the modulation of vascular tone and function. 6,7 Taken together, our results allow us to propose that, ROS/RNS excess in peripheral resistance vessels during I/R injury may blunt PI3K/Akt/eNOS pathway, thus triggering endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins from tissue and cell lysates were resolved by SDS/PAGE and immunoblotting as described (16,36). Primary antibodies used include the following: Dicer p-Ab (Abcam), ␤-actin m-Ab (Abcam), VE-CadherinpAb and Tsp1-pAb (Santa Cruz).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Akt (also known as PKB) is a family of three serine/threonine protein kinases (Akt1, Akt2, and Akt3) that regulate a host of cellular functions, including cell survival, proliferation, differentiation, and intermediary metabolism (5)(6)(7). Even though the majority of the literature does not make a distinction between different Akt isoforms, there is a growing list of differences between them.…”
mentioning
confidence: 99%
“…Akt1 appears not to be dispensable for eNOS induction and endothelial cell function (8,9), whereas Akt2 is not dispensable for insulin signaling (10). Deletion of Akt1 resulted in enhanced atherosclerosis in the APOE −/− mouse model (5), and Akt1 −/− mice do not develop endotoxin tolerance (11). Akt1 ablation protects and Akt2 ablation promotes MMTV-PyMT and MMTVErbB2-induced mammary tumors (12) and Akt1 −/− tumors, although very few, are more invasive as the result of microRNA expression differences (7).…”
mentioning
confidence: 99%